Adaptation and psychometric characteristics of a scale to evaluate ageist stereotypes. (September 2020) - Rosell, Javiera; Vergés, Alvaro; Torres Irribarra, David; Flores, Karina; Gómez, Macarena
Highlights: Negative ageism impacts on the well-being of older persons; therefore, its identification is important. The revised CENVE consists of 15 items with a unifactorial structure that showed good psychometric properties. It allows to perform a reliable evaluation of ageism in the Spanish-speaking population. The instrument gives the possibility to compare groups by age and gender. Revised CENVE will allow the identification of ageist stereotypes, a necessary step to develop interventions aimed to reduce them. Abstract: Objectives: Negative ageism impacts on the well-being of older persons; therefore, its identification is important to generate interventions that allow its decrease. CENVE is a widely used instrument to evaluate stereotypes towards old age in Spanish. However, its factor structure in older population and its invariance between those over and under 60 years old have not been confirmed. The objectives of the study are to evaluate the psychometric properties of the instrument and its invariance by age and gender. Methods: The total sample was 439 people with 54 % of people over 60. This was divided into two random subsamples. With the first subsample, a confirmatory factor analysis of the different models proposed was carried out until an adequate fit was achieved, which was confirmed with the second subsample. Then, the invariance of the instrument was evaluated with the total sample by age and gender. Results: The revised CENVE consists of 15 items with a unifactorial structure that showed good psychometric properties. It presented good reliability, including a .92 Omega. In addition, it proved to be an invariant instrument according to age and gender, which allows comparison between groups. Discussion and Implications: The use of CENVE will allow the identification of ageist stereotypes, with which interventions can be carried out to reduce them, both in groups older and younger than 60. In addition, it can be useful to generate a discussion about ageism in different fields, such as professional training.